1998
DOI: 10.1073/pnas.95.12.7040
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium VirD2 protein interacts with plant host cyclophilins

Abstract: Agrobacterium tumefaciens induces crown gall tumors on plants by transferring a nucleoprotein complex, the T-complex, from the bacterium to the plant cell. The Tcomplex consists of T-DNA, a single-stranded DNA segment of the tumor-inducing plasmid, VirD2, an endonuclease covalently bound to the 5 end of the T-DNA, and perhaps VirE2, a single-stranded DNA binding protein. The yeast two-hybrid system was used to screen for proteins interacting with VirD2 and VirE2 to identify components in Arabidopsis thaliana t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 52 publications
0
79
0
6
Order By: Relevance
“…For example, VirD2 binds three members of the Arabidopsis cyclophilin chaperone family; these interactions might maintain the proper conformation of VirD2 in the host-cell cytoplasm or nucleus during T-complex transit 79 . VirD2 also interacts with a serine/threonine phosphatase (PP2C) and, correspondingly, there is evidence for VirD2 phosphorylation in plant tissues.…”
Section: A Tumefaciens T-dna and Effector Protein Transfermentioning
confidence: 99%
“…For example, VirD2 binds three members of the Arabidopsis cyclophilin chaperone family; these interactions might maintain the proper conformation of VirD2 in the host-cell cytoplasm or nucleus during T-complex transit 79 . VirD2 also interacts with a serine/threonine phosphatase (PP2C) and, correspondingly, there is evidence for VirD2 phosphorylation in plant tissues.…”
Section: A Tumefaciens T-dna and Effector Protein Transfermentioning
confidence: 99%
“…AtCYP18-3 was shown to interact with Agrobacterium VirD2, an endonuclease covalently bound to the 59 end of the T-DNA. Because T-DNA transfer is inhibited by CsA, CYP interaction with VirD2 may be important for agrobacterial infection (Deng et al, 1998). AtCYP26-1 is another CYP predicted to be cytosolic.…”
Section: Genomic Organization and Phylogenetic Relationship Of Arabidmentioning
confidence: 99%
“…A cyclophilin 40 homolog has been shown to regulate development of leaf shape in Arabidopsis (Berardini et al, 2001). Several plant cyclophilins interact with an endonuclease involved in T-DNA transfer from agrobacterium to host plant cells (Deng et al, 1998). Disruption of AtFKBP42 gene function caused developmental defect (Kamphausen et al, 2002).…”
mentioning
confidence: 99%
“…Other plant proteins that were identified to interact with VirD2 include several cyclophilins, a kinase CAK2M, and a protein phosphatase 2C (PP2C). Deng et al (1998) showed that an Arabdopsis cyclophilin interacted strongly with VirD2. They further characterized the interaction domain of VirD2 and found that a central domain of VirD2 (residues 274~337) was involved in the interaction with cyclophilin.…”
Section: Plant Proteins Involved In T-complex Nuclear Targetingmentioning
confidence: 99%